An analysis of exchange rate pass-through to prices in South Africa - Karoro, Tapiwa Daniel (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2008)
The fact that South Africa has a floating exchange rate policy as well as an open trade policy leaves the country's import, producer and consumer prices susceptible to the effects of exchange rate movements. Given the central role that inflation targeting occupies in South Africa's monetary policy, it becomes necessary to determine the nature of influence of exchange rate changes on domestic prices. To this end, this thesis examines the magnitude and speed of exchange rate pass-through (ERPT) to import, producer and consumer prices in South Africa. Furthermore, it explores whether the direction and size of changes in the exchange rate have different pass-through effects on import prices, that is, whether the exchange rate pass-through is symmetric or asymmetric. The paper uses monthly data covering the period January 1980 to December 2005. In investigating ERPT, two main stages are identified. The initial stage is the transmission of fluctuations in the exchange rate to import prices, while the second-stage entails the pass-through of changes in import prices to producer and consumer prices. The first stage is estimated using the Johansen (1991) and (1995) cointegration techniques and a vector error correction model (VECM). The second stage pass-through is determined by estimating impulse response and variance decomposition functions, as well as conducting block exogeneity Wald tests. The study follows Wickremasinghe and Silvapulle's (2004) approach in estimating pass-through asymmetry with respect to appreciations and depreciations. In addition, the thesis adapts the analytical framework of Wickremasinghe and Silvapulle (2004) to investigate the pass-through of large and small changes in the exchange rate to import prices. The results suggest that ERPT in South Africa is incomplete but relatively high. Furthermore, ERPT is found to be higher in periods of rand depreciation than appreciation which supports the binding quantity constraint theory. There is also some evidence that pass-through is higher in periods of small changes than large changes in the exchange rate, which supports the menu cost theory when invoices are denominated in the exporters' currency.
Keywords: Foreign exchange rates -- South Africa; Monetary policy -- South Africa; Inflation (Finance) -- South Africa; Prices -- South Africa; Banks and banking -- South Africa; South Africa -- Economic policy